ANALYSIS OF SANCTIONS ON CHELSEA FC: THE IMPACT OF THE RUSSIA-UKRAINE CONFLICT ON SPORTS CLUB OWNERSHIP - Meganingratna, Andi; Maulana, Achmad Amzal (BHUVANA: Journal of Global Studies, 2025)
This research examines the complex relationship between sports and international politics through the case study of sanctions imposed on Chelsea FC in the context of the Russia-Ukraine conflict. This study aims to analyze how international conflicts can affect individual entities, particularly in terms of football club ownership. Utilizing the theory of complex interdependence as proposed by Keohane and Nye, this study employs a qualitative methodology with an explanatory case study approach, analyzing official documents from the UK government, Chelsea FC’s documentation, and international media coverage. The findings indicate that the application of smart sanctions against Chelsea FC through its owner, Roman Abramovich, reflects a significant evolution in the use of foreign policy instruments. Three main dimensions of British interest are identified: economic, aimed at disrupting the financial flows of Russian oligarchs; political, to strengthen the United Kingdom’s position in the post-Brexit landscape; and sociocultural, leveraging the Premier League as a form of soft power. This research contributes to demonstrating how modern sports have transformed into an integral part of the complex web of international relations.